Magnetic Memory Effect in La0.6Sr0.4MnO3 Perovskite Nanoparticles - Nam, Nguyen Hoang; Luong, Nguyen Hoang (VNU Journal of Science: Mathematics - Physics; Vol 30 No 3, 2014)
Abstract: Magnetic memory effect was newly observed in spin-glass magnetic La 0.6 Sr 0.4 MnO 3 perovskite nanoparticles prepared by sol-gel method. The applied magnetic field and the temperature were changed in defined protocols during the magnetic relaxation process and the magnetic memory effect occured at temperature below blocking temperature which is around room temperature. This magnetic memory effect can be explained by the energy distribution in comparison with strong interaction systems. Keywords: Perovskite nanoparticles, magnetic memory effect , sol-gel, magnetic properties.